2012
DOI: 10.1620/tjem.226.275
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Protects Cardiomyocytes from Myocardial Ischemia-Reperfusion Injury by Enhancing Phosphorylation of Apoptosis Repressor with Caspase Recruitment Domain

Abstract: Hydrogen sulfide (H 2 S) displays an anti-apoptotic activity against myocardial ischemia reperfusion (MIR). Apoptosis repressor with caspase recruitment domain (ARC) is constitutively expressed in the heart and inhibits cell apoptosis when it is phosphorylated. Here, we investigated whether H 2 S could inhibit apoptosis by affecting ARC phosphorylation using cultured rat cardiomyocytes and a rat model of MIR. Primary cardiomyocytes were prepared from hearts of newborn rats and were pre-incubated with NaHS, a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
0
16
2
3
Order By: Relevance
“…H2S reduced calcineurin activity and the expression levels of Fas, FasL and cleaved caspase-3 proteins (Yao et al, 2012). More specifically, during the early PC period, H2S increased the nuclear localization of Nrf2, a transcription factor that regulates the gene expression of a number of antioxidants and increased the phosphorylation of PKCε and STAT-3.…”
Section: Experimental Model Effect Of H2s Proposed Mechanism(s) Refermentioning
confidence: 92%
See 4 more Smart Citations
“…H2S reduced calcineurin activity and the expression levels of Fas, FasL and cleaved caspase-3 proteins (Yao et al, 2012). More specifically, during the early PC period, H2S increased the nuclear localization of Nrf2, a transcription factor that regulates the gene expression of a number of antioxidants and increased the phosphorylation of PKCε and STAT-3.…”
Section: Experimental Model Effect Of H2s Proposed Mechanism(s) Refermentioning
confidence: 92%
“…NaHS administration before sustained ischaemia resulted in a remarkable reduction of the infarct size (Zhuo et al, 2009) and significantly reduced cell apoptosis (Sivarajah et al, 2009;Yao et al, 2012). Furthermore, a single bolus of NaHS administered 24 h before myocardial infarction produced a strong infarct-limiting effect and a time-course study demonstrated that the protection lasted for at least 3 days after the PC stimulus (Pan et al, 2009).…”
Section: Cardioprotection By Exogenous H 2 S Administrationmentioning
confidence: 99%
See 3 more Smart Citations